(STRESS SOCIETY RESULTS FROM DIESEL ENGINE NOISE SOUND INTENSITY OF ANI MAL FEED MILL COW: STUDY RURAL COMMUNITY PANDANTOYO KEDIRI) - Moch. Maftuchul Huda; Intan Novita Ayu Prasetyowati (NurseLine Journal, 2016)
Noise is audible voice but not desired. Noise becomes the source of the stress. One source of noise in the community is the diesel engine milling cattle feed.The purpose of research to identify the relation of diesel engine noise intensity grinding cattle feed withthe level of stress on the society of Pandantoyo village, Ngancar district Kediri regency. The design of the study is case control study with retrospective approach. Sampling technique used purposive sampling with a sample of 20 respondents. Data was obtained using instruments stress. The results almost entirely (80%) of respondents with intensity 80-100 dB noise was very hustle categories, the majority (60%) experienced medium stress levels, a small portion (20%) levels of stress. Spearman rho test results was ob tained (p value 0.01 < 0.05, cc: + 0.515), means that there are correlation between the intensity of noise stress levels, for a positive relation with medium strength. When our bodies are stimulated intensity noise impacted to the stress, and will activate the sympa